A Georgian and an Iranian new species of Renea G. Nevill, 1880 enormously extend the genus’s distribution (Gastropoda: Caenogastropoda: Aciculidae) - Páll-Gergely, Barna; Grego, Jozef (Zootaxa, 2022)
Renea caucasica n. sp. and R. nemethi n. sp. are described from Georgia and northern Iran, respectively. Since the genus Renea has been reported from an area between south-eastern France and southern Albania, these two species extend the distribution of Renea eastwards enormously.